KONSELING KELOMPOK DENGAN PENDEKATAN EKSISTENSIAL-HUMANISTIK UNTUK MELATIH PENYESUAIAN DIRI MELALUI RANDAI DARI MINANGKABAU [GROUP COUNSELING USING AN EXISTENTIAL-HUMANISTIC APPROACH TO DEVELOP SELF-ADJUSTMENT COMBINED WITH THE EXPRESSIVE ARTS TECHNIQUES OF RANDAI OF MINANGKABAU] - Afra Hasna (Polyglot, 2019)
Group counseling is a group therapeutic activity to help the counselee identify problems, find alternatives using problem- solving and decision-making, and then act. The existential-humanistic approach in group counseling aims at influencing the counselee to focus on human nature, including the ability to be self-aware, self-determined, and responsible. For clients that need help with self-adjustment, counseling can be combined with the expressive arts techniques of Randai (a folk theatre tradition of the Minangkabau ethinic group in West Sumatra). The application of Randai can be done at the working stage. Using Randai, clients can be trained to be cautious, compact, cooperative, diligent, and optimistic.ABSTRAK: Konseling kelompok merupakan kegiatan terapeutik berkelompok guna membantu konseli mengidentifikasi, menemukan alternatif pemecahan masalah dan pengambilan keputusan dan mewujudkannya. Pendekatan eksistensial-humanistik dalam konseling kelompok bertujuan mempengaruhi konseli berfokus pada sifat manusia mencakup kesanggupan untuk menyadari diri, bebas menentukan nasib sendiri, dan bertanggungjawab. Dalam praktik konseling dikolaborasikan dengan kegiatan randai dari Minangkabau sebagai upaya melatih penyesuaian diri. Penerapan randai dilaksanakan pada tahap kerja (working stage). Dalam randai, klien dilatih bersikap hati-hati, kompak, kerjasama, tekun dan optimis.